The Library of the Metropolitan Seminary and the Faculty of Theology (Teología, 2018)
Words pronounced by the Director, of the Library Pbr. Dr. Fernando Gil, on the occasion of the blessing of the Library's enlargements, on April 18, 2017.
Keywords: Theology Libraries; History of Libraries